The Role of Organizational Citizenship Behaviour in Mediating The Effect of Green Transformational Leadership On Green Performance Pt Anugerah Tirta Samudra - Prastyorini, Juli (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to test and analyse the direct and indirect effects of Green Transformational Leadership on employee Green Performance through Organizational Citizenship Behavior at PT Anugerah Tirta Samudra (Artamuda). The variables used in this study are Green Transformational Leadership as the independent variable, Organizational Citizenship Behaviour as the intervening variable and Green Performance as the dependent variable. This type of research is explanatory research. The number of samples used in t he study were 32 employees of PT Anugerah Tirta Samudra (Artamuda) with the sampling technique used, namely saturated sampling, where all members of the population were used as research samples. The data analysis technique used is using path analysis using SmartPLS. The results show that Green Transformational Leadership both directly and indirectly through Organizational Citizenship Behaviour has a significant and positive influence on the Green Performance of employees of PT Anugerah Tirta Samudra (Artamu da)